2017
DOI: 10.1371/journal.pone.0181711
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of angiotensin-regulating enzymes is associated with prognostic outcome in clear cell renal cell carcinoma patients

Abstract: The discovery of the intrarenal renin-angiotensin system (iRAS), which regulates angiogenesis, cell differentiation and proliferation, has opened new perspectives in the knowledge of kidney carcinogenesis. In this study we analyzed the immunohistochemical expression and fluorimetric activity of four key peptidases of iRAS in tumor tissue (n = 144) and serum samples (n = 128) from patients with renal neoplasms. Neutral endopeptidase (NEP/CD10), Angiotensin-converting enzyme-2 (ACE2), and aminopeptidase A (APA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 51 publications
5
35
0
3
Order By: Relevance
“…Consequently, changes in topology and ACE expression levels in cancer may serve as a marker localization effects proonkogennyhA-2 and other humoral factors, the metabolism of which is associated with the functions of RAS components. For example, in cancer of the kidneys, a regular change in protein expression and activity of ACE topology (Errarte P. et al, 2017;. Sobczuk P. et al, 2017).…”
Section: Angiotensin-i-converting Enzyme (Ace-1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, changes in topology and ACE expression levels in cancer may serve as a marker localization effects proonkogennyhA-2 and other humoral factors, the metabolism of which is associated with the functions of RAS components. For example, in cancer of the kidneys, a regular change in protein expression and activity of ACE topology (Errarte P. et al, 2017;. Sobczuk P. et al, 2017).…”
Section: Angiotensin-i-converting Enzyme (Ace-1)mentioning
confidence: 99%
“…Sobczuk P. et al, 2017). Normally cortical epithelium tubule of the nephron segments, in particular, epithelium proximal demonstrates high expression indicators ACE that is not in clear cell renal cell carcinoma (CCRCC) and is detected only in the tumor blood vessels (Errarte P. et al, 2017). The authors have shown that the protein expression level in the tumor and the magnitude of its enzymatic activity in blood plasma may be a marker CCRCC aggressiveness and overall survival of CCRCC patients.…”
Section: Angiotensin-i-converting Enzyme (Ace-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Метаболический дисбаланс компонентов внутрипочечной РАС при опухолях почек показан в нескольких исследованиях [11,12]. При изучении экспрессии АПФ и АПФ2 продемонстрирована значительная корреляция их повышенной активности с агрессивностью светлоклеточного почечно-клеточного рака [13]. Однако в другом исследовании установлено, что ферментативная активность и экспрессия АПФ и АПФ2 в основном подавляются в тканях почечно-клеточного рака и хромофобного РП, а также при почечной онкоцитоме, а уровни АПФ2 и матричной РНК снижены только при хромофобном и онкоцитарном РП, а при почечно-клеточном раке не коррелируют [14].…”
Section: Introductionunclassified
“…Однако показано, что нарушения локальной экспрессии компонентов РАС сопряжены с опухолевым ростом в почках [5,6]. Так, повышенная тканевая экспрессия ангиотензинрегулирующих ферментов (АПФ и АПФ2) сопряжена с агрессивностью почечно-клеточного рака [7].…”
unclassified